Stereotactic radiosurgery of early melanoma brain metastases after initiation of anti-CTLA-4 treatment is associated with improved intracranial control. Issue 1 (October 2017) - An, Yi; Jiang, Wen; Kim, Betty Y.S.; Qian, Jack M.; Tang, Chad; Fang, Penny; Logan, Jennifer; D'Souza, Neil M.; Haydu, Lauren E.; Wang, Xin A.; Hess, Kenneth R.; Kluger, Harriet; et al.
Abstract: Background: Numerous studies suggest that radiation can boost antitumor immune response by stimulating release of tumor-specific antigens. However, the optimal timing between radiotherapy and immune checkpoint blockade to achieve potentially synergistic benefits is unclear. Material and methods: Multi-institutional retrospective analysis was conducted of ninety-nine metastatic melanoma patients from 2007 to 2014 treated with ipilimumab who later received stereotactic radiosurgery (SRS) for new brain metastases that developed after starting immunotherapy. All patients had complete blood count acquired before SRS. Primary outcomes were intracranial disease control and overall survival (OS). Results: The median follow-up time was 15.5 months. In the MD Anderson cohort, patients who received SRS after 5.5 months ( n  = 20) of their last dose of ipilimumab had significantly worse intracranial control than patients who received SRS within 5.5 months ( n  = 51) (median 3.63 vs. 8.09 months; hazard ratio [HR] 2.07, 95% confidence interval [CI] 1.03–4.16, p  = 0.041). OS was not different between the two arms. The improvement in intracranial control was confirmed in an independent validation cohort of 28 patients treated at Yale-New Haven Hospital. Circulating absolute lymphocyte count before SRS predicted for treatment response as those with baseline counts >1000/µL had reduced risk of intracranial recurrence compared with those with ≤1000/µL (HR 0.46, 95% CI 0.0.23–0.94, p  = 0.03). Conclusions: In this multi-institutional study, patients who received SRS for new brain metastases within 5.5 months after ipilimumab therapy had better intracranial disease control than those who received SRS later. Moreover, higher circulating lymphocyte count was associated with improved intracranial disease control.